Modeling economic development decision-making: the case of tax abatements - Reese, Laura A. (1999)
This research note examines two models of economic development policy making. The literature on economic development and urban politics provides one image of reality regarding the factors associated with economic development policy in cities. When tested empirically, however, this model is found wanting. An alternative model is presented, identifying the complex set of factors associated with a single governmental policy, in this case, tax abatements. - Reproduced
Keywords: Taxation; Economic and social development